Navigating Therapeutic Desperation: A Qualitative Retrospective on the Nanyonga Soil-Healing Phenomenon and Medical Pluralism During Uganda's Early HIV/AIDS Crisis - Joseph Kikomeko (East African Journal of Health and Science, 2026)
This qualitative retrospective case study investigates the Nanyonga soil-healing phenomenon as a community-driven therapeutic response during the peak of Uganda's early HIV/AIDS epidemic in late 1989. Centred in Ntuku Village, Mawogola County, Sembabule District, this sudden, massive movement emerged under acute therapeutic desperation, characterised by a complete absence of antiretroviral therapy, severe resource constraints, high mortality, and pervasive social stigma. Over several weeks, an estimated hundreds of thousands of individuals travelled to Sembabule and consumed approximately 45 tons of soil distributed by Yowanina Nanyonga, a 60-year-old devout Catholic peasant who claimed a divine visitation instructing her to dispense soil to cure all illnesses, including AIDS. This study explores the socio-cultural, clinical, and institutional dynamics of this mass geophagic phenomenon. Guided by Institutional Theory and Medical Pluralism Theory, data were collected through semi-structured, in-depth interviews with 20 purposively selected participants (5 traditional healers, 6 biomedical practitioners, 4 healthcare policymakers, and 5 community members). Crucially, 14 participants possessed direct first-hand experience of the late 1989 events. To address retrospective limitations and mitigate recall bias, participant testimonies were systematically validated and triangulated with 1989 historical print media (specifically daily editions of The New Vision and The Weekly Topic) and district-level health archives. The study reveals that severe therapeutic desperation catalysed the immediate social legitimacy and rapid mobilisation of Nanyonga's soil healing, as informal cultural-cognitive institutions stepped in to provide communal hope and emotional solace where formal structures could offer only clinical diagnostics and palliative containment. Furthermore, patients practised pragmatic medical pluralism, combining folk remedies with formal hospital care simultaneously rather than rejecting modern science. While soil healing offered critical psychological support and social solidarity, the geophagic practice of ingesting untreated soil posed severe clinical risks. Ingestion of raw soil exposed vulnerable, immunocompromised populations to Soil-Transmitted Helminths (Ascaris lumbricoides, Trichuris trichiura) and bacterial pathogens (Clostridium tetani). Biologically, clay-rich geophagic soils (rich in kaolinite) act as powerful mineral binders in the gut, adsorbing essential divalent cations like iron (Fe2+) and zinc (Zn2+), directly inducing or severely exacerbating iron-deficiency anaemia—a clinically catastrophic result for HIV/AIDS patients. These findings highlight the critical need for pluralistic health governance frameworks that move beyond symbolic recognition or binary exclusion. Sustainable epidemic preparedness demands structured mechanisms for collaborative research, culturally competent health systems, and non-stigmatising public communication to ensure both clinical safety and cultural accountability in pluralistic systems.